LAJU TRANSPIRASI TUMBUHAN DOMINAN PASCA KEBAKARAN LAHAN GAMBUT DAN PEMANFAATANNYA UNTUK RANCANGAN MEDIA FLIPCHART BIOLOGI SMA - Novia Lori Afni Nababan; Firdaus LN '; Sri Wulandari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to determine the characteristics of transpiration of dominant plants post fire peatland in Rimba Panjang Village, Kampar District. The results of the research will be utilized for flipchart media design of the influence of external factors on the growth and development of plants in Class XII Senior High School. This research was conducted in February-June 2017 by using 2 phases namely (1) Stage measurement of transpiration rate of dominant plants; (2) Stage design of Senior High School Biology flipchart media. The research used survey method with observation in Rimba Panjang Village, Kampar District. Determination of sampling location was done by purposive random sampling based on the gradient of fire time and the samples were taken by using the line method. Flipchart media design is done by analysis and design phase. The main parameters in this study were the transpiration rate of dominant plants of sapling level and environmental factors namely soil moisture, light intensity, temperature and humidity as supporting parameters. The results showed that the transpiration characteristics of dominant plants after fire were influenced by the time of the fire. The transpiration rate tends to decrease from the observation site with the longest fire incident time (2009) to the new site experiencing the fire incident (2017). After a fire incident, plants need time to recover from damage both in function and physiology of plants. Differences in environmental conditions at each site with a gradient time observation of the fire is influenced by the high and low intensity fires. Based on the research results developed as a teaching material that will be presented in the design of Senior High School Biology flipchart media.Key Word: Peatland, Transpiration Rate, Flipchart Media2